The effect of the application of boron in soils of the "cerrado" vegetation - Laun, Carlos R. P.; Brasil Sobrinho, Moacyr O. C. do; Igue, Toshio (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
The present was carried out with the objective of studying the effects of boron applications on Red Yellow Latosol - sandy phase and on Regossol (Quartzosas Sand) under "Cerrado" vegetation of São Simão, São Paulo, State. Chemical determinations of soluble boron were made on soil samples of the experimental area collected before and after dolomitic line applications. Complementary biological tests of boron were also made, employing sunflower (Helianthus annus L.). Simultaneously, fold experiment was carried and with dry (Phaseolus vulgaris L.) to study boron applications. The main conclusions were the followings: 1 - Biologycal tests with sumflower were correlated with chemical analysis indicating that both soil units were slightly or no boron deficient. 2 - The soil classified how Regosol (Quartzous Sand) showed a larger Boron content than the Red Yellow Latosol-sandy phase. 3 - There has been no response of dry beans to boron on both soils.